2014
DOI: 10.3109/21681805.2014.971427
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of interleukin-2 receptor and interleukin-6 in patients with prostate cancer and benign prostatic hyperplasia: Association with asymptomatic inflammatory prostatitis NIH category IV

Abstract: IL-2R and IL-6 expression was significantly higher in prostate cancer tissue than in normal tissue. Patients with asymptomatic inflammatory prostatitis NIH category IV showed significantly greater activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 34 publications
2
16
1
Order By: Relevance
“…Even though some of the literature has showed that CP/ CPPS is an important health issue in elder population, [25][26][27][28] the present study failed to observe such an association between CP/CPPS and previous colonoscopy in the elderly (≥60 years old). According to anatomical and physiological changes of the prostate in the elderly, a portion of the pathogenesis of prostate inflammation differs from that in young adults.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Even though some of the literature has showed that CP/ CPPS is an important health issue in elder population, [25][26][27][28] the present study failed to observe such an association between CP/CPPS and previous colonoscopy in the elderly (≥60 years old). According to anatomical and physiological changes of the prostate in the elderly, a portion of the pathogenesis of prostate inflammation differs from that in young adults.…”
Section: Discussioncontrasting
confidence: 97%
“…We first excluded all subjects who had a history of CP/CPPS since the beginning of the NHI program in 1995. Thereafter, we selected 3933 controls matched with cases by age group (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)30-39, 40-49, 50-59, 60-69, and >69 years) and index year. We selected the controls by matching them to a given CP/CPPS case simply due to use of medical services in the same index year of that particular case.…”
Section: Selection Of Cases and Controlsmentioning
confidence: 99%
“…The authors' previously published data about the incidence of NIH IV prostatitis revealed asymptomatic NIH IV prostatitis in 43.8% of the patients with PCa and 70.7% of the patients with BPH [14,30]. According to a PubMed search, the presented data analysis is the first showing a direct association between asymptomatic inflammatory prostatitis NIH category IV, the incidence of prostatic calcification and elevated TNF-a expression in patients with obstructive BPH treated by TURP.…”
Section: Discussionmentioning
confidence: 82%
“…Evidence for the importance of estrogen, by way of increasing interferon-mRNA and interleukin (IL-2, IL-4, IL-6, IL-7, IL-8 IL-15, IL-17) in BPH can be found [6][7][8][9][10]14]. Tumor necrosis factor-a (TNF-a) is an adipokine responsible for systemic inflammatory reactions.…”
Section: Introductionmentioning
confidence: 99%
“…In gastric cancer cells, IL-1 may enhance the invasiveness of cancer cells through the IL-6 expression [63]. The immunohistochemical expression of IL-2 receptor and IL-6 is higher in prostate cancer tissue than in normal tissue [64]. IL-6 gene polymorphism is associated with increased risk of bladder cancer [65].…”
Section: The Rationale Of Developing Anti-il-6 For the Clinical Theramentioning
confidence: 99%